Admicellar Polymerization of Tris(2-acryloyloxyethyl)phosphate on Cotton Fabric for Flame Retardant Finishing - Dahiya, J.B.; Dinesh (Asian Journal of Chemistry, 2022)
To improve the flame retardant property, the admicellar polymerization process was applied to polymerize and coat the tris(2-acryl-oyloxyethyl)phosphate (PTAP) monomer on cotton fabric (CF). The polymerization was completed with the support of a cationic surfactant cetyltrimethylammonium bromide (CTAB) and an initiator 2,2′-azobisisobutyronitrile (AIBN). Thermogravimetric analysis (TGA) and limiting oxygen index test (LOI) were performed to find out the effects on degradation and flammability of modified cotton fabric. One of the modified cotton fabric samples (CF-PTAP) show the decrease in onset temperature caused by acid catalyzed dehydration released from PTAP polymer placed on cotton fabric substrate. The increase in char yield (20.9%) and LOI value (25.0% demonstrated a condensed phase flame retardant action) owing to the presence of PTAP polymer on substrate.